Immuno-inflammatory in vitro hepatotoxicity models to assess side effects of biologicals exemplified by aldesleukin - Roser, Luise A.; Luckhardt, Sonja; Ziegler, Nicole; Thomas, Dominique; Wagner, Pia Viktoria; Damm, Georg; Scheffschick, Andrea; Hewitt, Philip; Parnham, Michael J.; Schiffmann, Susanne (Frontiers in Immunology, 2023)
Hepatotoxicity induced by immunotherapeutics is an appearing cause for immune-mediated drug-induced liver injury. Such immuno-toxic mechanisms are difficult to assess using current preclinical models and the incidence is too low to detect in clinical trials. As hepatotoxicity is a frequent reason for post-authorisation drug withdrawal, there is an urgent need for immuno-inflammatory in vitro models to assess the hepatotoxic potential of immuno-modulatory drug candidates. We developed several immuno-inflammatory hepatotoxicity test systems based on recombinant human interleukin-2 (aldesleukin). Co-culture models of primary human CD8+ T cells or NK cells with the hepatocyte cell line HepaRG were established and validated with primary human hepatocytes (PHHs). Subsequently, the HepaRG model was refined by increasing complexity by inclusion of monocyte-derived macrophages (MdMs). The main readouts were cytotoxicity, inflammatory mediator release, surface marker expression and specific hepatocyte functions. We identified CD8+ T cells as possible mediators of aldesleukin-mediated hepatotoxicity, with MdMs being implicated in increased aldesleukin-induced inflammatory effects. In co-cultures of CD8+ T cells with MdMs and HepaRG cells, cytotoxicity was induced at intermediate/high aldesleukin concentrations and perforin was upregulated. A pro-inflammatory milieu was created measured by interleukin-6 (IL 6), c-reactive protein (CRP), interferon gamma (IFN γ), and monocyte chemoattractant protein-1 (MCP¬ 1) increase. NK cells responded to aldesleukin, however, only minor aldesleukin-induced cytotoxic effects were measured in co-cultures. Results obtained with HepaRG cells and with PHHs were comparable, especially regarding cytotoxicity, but high inter-donor variations limited meaningfulness of the PHH model. The in vitro test systems developed contribute to the understanding of potential key mechanisms in aldesleukin-mediated hepatotoxicity. In addition, they may aid assessment of immune-mediated hepatotoxicity during the development of novel immunotherapeutics.